Isolated zeros destroy Fermi surface in holographic models with a lattice - Floris Balm; Alexander Krikun; Aurelio Romero-Bermúdez; Koenraad Schalm; Jan Zaanen (Journal of High Energy Physics)
Abstract We study the fermionic spectral density in a strongly correlated quantum system described by a gravity dual. In the presence of periodically modulated chemical potential, which models the effect of the ionic lattice, we explore the shapes of the corresponding Fermi surfaces, defined by the location of peaks in the spectral density at the Fermi level. We find that at strong lattice potentials sectors of the Fermi surface are unexpectedly destroyed and the Fermi surface becomes an arc-like disconnected manifold. We explain this phenomenon in terms of a collision of the Fermi surface pole with zeros of the fermionic Green’s function, which are explicitly computable in the holographic dual.